Effect of physical exercise on non-linear parameters of heart rate variability in Chronic Obstructive Pulmonary Disease - Tasnim, Syeda Fadia; Begum, Shelina; Sultana, Shamima; Islam, Shams Ruhani (Journal of Bangladesh Society of Physiologist, 2022)
Background: Chronic Obstructive Pulmonary Disease (COPD) is associated with autonomic nerve dysfunction. Nonlinear methods of heart rate variability (HRV) analysis have been gaining interest as a method of detecting changes in cardiac autonomic nerve function. Regular practice of physical exercise may cause improvement of this impaired autonomic nerve function. Objectives: To assess the effect of physical exercise on nonlinear measures of HRV analysis in male patients with COPD. Methods: This prospective interventional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka in 2018 on 60 diagnosed male COPD patients aged 40-75 years with disease duration of at least 5 years selected from the Department of Respiratory Medicine, BSMMU, Dhaka. Thirty patients underwent physical exercise (walking for 30 minute and pursed lip and diaphragmatic breathing 10 minuts)for 3 months in addition to standard treatment. Thirty (30) patients received only standard treatment for 3 months. For comparison, 30 age matched apparently healthy males were also enrolled. HRV data of all patients were recorded before and after 3 months of follow up. HRV data of healthy controls were recorded once at baseline. For assessing autonomic dysfunction, nonlinear parameters of HRV were recorded by Power Lab 8/35. For statistical analysis, paired sample t-test and independent sample t-test were done as applicable. Results: SD1, SD2 and SD1/ SD2 were found significantly lower in COPD patients compared to healthy controls at baseline. After 3 months of physical exercise, significant increment of these parameters occurred with a trend of improvement in cardiac autonomic nerve function in these patients. Conclusion: This study concluded that physical exercise can improve cardiac autonomic nerve dysfunction function in COPD patients. J Bangladesh Soc Physiol. 2022, June; 17(1): 6-13